Agama Dalam Perspektif Psikologi : Study Di Sdit Nuurul A’raaf Islamic School, Cikarang Selatan, Bekasi. - Adhya Putri Maharani; Amaliyah Fitriyani; Laraswati Laraswati; Noor Azida Batubara (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines how religious education is understood and enacted through a psychological lens at SDIT Nuurul A’raaf, Cikarang Selatan, Bekasi. Employing a qualitative case study design, participants included the principal, one Islamic Education teacher, and 8–10 upper-grade students. Data were gathered via semi-structured interviews, participant observation of communal dhuha prayer, morning Qur’an recitation, and daily supplication, as well as document review; data were thematically analyzed with triangulation and member checking. Findings indicate an integrative model in which psychology informs children’s emotional and developmental needs while religion provides meaning and ritual structure. Teacher differentiation personal dialogue, empathic support, and value-laden storytelling was associated with higher motivation, prayer discipline, and improved emotional regulation; the classroom climate was supportive with minimal punishment-based control. Results suggest that religion functions as a positive force for children’s emotional well-being and prosocial behavior, with communal rituals acting as reinforcers of habits. The study recommends strengthening teachers’ micro-counseling skills, balancing the ritual calendar for variety and repetition, and conducting longitudinal evaluation to assess sustained impacts.